1978
DOI: 10.1073/pnas.75.4.1971
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by membrane sialic acid of β1H-dependent decay-dissociation of amplification C3 convertase of the alternative complement pathway

Abstract: Sheep erythrocytes in their native state did not activate the alternative complement pathway, as measured by Iysis in dilutions of normal human serum containing [ethyl-enebis(oxyethylenenitrilo)J tetraacetic acid but acquired this capacity after membrane sialic acid residues had been removed (by sialidase) or modified (by NaIO4). Activation of the alternative pathway by sheep erythrocytes required removal or modification of at least 40% of the membrane sialic acid to reach threshold, and it increased proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
231
0
4

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(242 citation statements)
references
References 37 publications
6
231
0
4
Order By: Relevance
“…Early studies showed that regulation of alternative pathway activation on targets was quantitatively different from that on host cells (61). This was later shown to be due to the presence of sialic acids or other polyanions on nonactivating cells (47,48) and this was subsequently shown to be due to polyanion recognition by factor H (37). Clinical evidence has appeared in recent years indicating that alleles and mutations that affect polyanion recognition domains in factor H result in pathology involving complement activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies showed that regulation of alternative pathway activation on targets was quantitatively different from that on host cells (61). This was later shown to be due to the presence of sialic acids or other polyanions on nonactivating cells (47,48) and this was subsequently shown to be due to polyanion recognition by factor H (37). Clinical evidence has appeared in recent years indicating that alleles and mutations that affect polyanion recognition domains in factor H result in pathology involving complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal site has also been shown to bind sialic acids (25,34). Interactions with polyanions are important because the 10-fold higher affinity of factor H for C3b on host cells and other nonactivators (47,48) requires the presence of sialic acid clusters or other polyanions on the surface. The polyanion binding site in domain 7 has been strongly associated with a disease of the retina, age-related macular degeneration, suggesting the possibility of tissue specific polyanion recognition by individual sites of factor H (49 -52).…”
mentioning
confidence: 99%
“…It is known that the terminal sugars on the glycoproteins on the surface of RBC in addition to some associated serum proteins are important factors to activate the AP. RaRBC are missing sialic acid and therefore make them excellent test cells to assay AP complement activity (Fearon, 1978;Dijk et al, 1985;Sunyer and Tort, 1995). Sheep RBC, on the other hand, have a lot of sialic acid, and this is one aspect of their inability to activate the AP and be lyzed by the terminal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Isopropyl alcohol-precipitated RNA was dissolved in diethylpyrocarbonate-treated water, and 1 g of RNA was denaturated at 70°C for 10 min and then immediately chilled on ice. Reverse-transcriptase reactions were conducted using RNA in a total volume of 20 l containing 10 mM DTT (Life Technologies), 500 M dNTP mix (Pharmacia), 25 g/ml oligo(dT) [12][13][14][15][16][17][18] (Pharmacia), and 200 U Moloney murine leukemia virus reverse transcriptase (Life Technologies) in a reverse-transcriptase buffer (Life Technologies). The reaction was allowed to occur for 1 h at 37°C.…”
Section: Rt-pcr Analysismentioning
confidence: 99%